The superficial and deep inferior epigastric artery composite perforator flap for breast reconstruction: A case report. Issue 7 (22nd October 2018) - Gassman, Andrew A.; Pan, Judy; Acevedo, Edwin; Haddock, Nicholas; Teotia, Sumeet
Abstract : The superficial inferior epigastric artery (SIEA) flap and the deep inferior epigastric perforator (DIEP) flap have been increasingly adopted for breast reconstruction; however, each have its own set of advantages and disadvantages. In the select subset of patients that cannot tolerate minimal abdominal fasciotomy that occurs with DIEP harvest and do not have adequate pedicle length that often occurs after SIEA harvest, we suggest another option for abdominally‐based free flap breast reconstruction. Here, we describe the formation of a composite perforator based on the pedicle of the retro‐rectus deep inferior epigastric vessels and the superficial inferior epigastric vessels, known as a superficial and deep inferior epigastric artery (SADIE) flap, which allows for a more compatible anastomotic size match than the SIEA and elongation of the vascular pedicle with minimal dissection of the anterior rectus fascia. Our patient is a 36 year‐old female (BMI = 24) with a history of breast cancer who subsequently underwent skin‐sparing mastectomy with tissue expander, chemotherapy, and eventual superior and deep inferior epigastric artery (SADIE) composite flap. The patient had an uncomplicated postoperative course at 6‐month follow‐up with excellent cosmesis. This modification in surgical technique has not been previously described in the literature and represents a suitable option for those desiring breast reconstruction, but have short pedicle length at harvest and cannot tolerate abdominal fasciotomy.